دور استخدام نظم المعلومات المحاسبيَّة في تحسين الميزة التنافسيَّة "دراسة ميدانيَّة على المصارف العاملة في السَّاحل السُّوري" (Latakia University Journal - Economic and Legal Sciences Series, 2019)
جاء هذا البحث للوقوف على مدى تأثير استخدام نظم المعلومات المحاسبيَّة في تحسين الميزة التنافسيَّة بأبعادها الخمسة (الجودة، التَّكلفة، المرونة، السُّرعة والإبداع)، وذلك في عيِّنة من المصارف العاملة في السَّاحل السُّوري. قام الباحثان بتوزيع (110) استبياناً على عيِّنة من المديرين ورؤساء الأقسام والمراقبين وأفراد الكوادر الإداريَّة المسؤولة عن اتِّخاذ أشكال وأنواع مختلفة من القرارات المعتمد في اتِّخاذها على المعلومات المحاسبيَّة في المصارف محل الدراسة، وقد بلغ عدد الاستبانات المستردَّة والصَّالحة للتَّحليل والَّتي تمَّ تفريغها (88) استبانة. قام الباحثان بتحليل البيانات باستخدام برنامج التَّحليل الإحصائي (SPSS 20). وفي نهاية هذا البحث توصَّل الباحثان إلى مجموعة من الاستنتاجات وأهمّها: يوجد تأثير معنوي لاستخدام نظم المعلومات المحاسبيَّة على تحسين الأبعاد الخمسة للميزة التنافسيَّة في المصارف محل الدراسة. كما تقدَّم الباحثان في نهاية البحث بمجموعة من التَّوصيات والَّتي كان أهمُّها: ضرورة تطبيق نظم المعلومات المحاسبيَّة في المصارف محل الدراسة، والاهتمام بتدريب المديرين والعاملين ومتَّخذي القرارات فيها على استخدام هذه النظم وزيادة معارفهم بمجالات استخدام الحاسوب والبرامج ذات العلاقة، كما يجب على إدارة المصارف محل الدراسة العمل على التَّحسين المستمر لنمط التِّقانة المستخدم والمرافق والتَّجهيزات والأدوات والمعدَّات التِّقنية والإداريَّة الخاصَّة بهذه المصارف. This research was conducted to determine the effect of the use of accounting information systems on improving the five-dimensional competitive advantage (quality, cost, flexibility, speed and creativity) in a sample of banks operating in the Syrian coast. The researcher distributed (110) questionnaires to managers, heads of departments, observers and administrative personnel responsible for taking various forms and types of decisions adopted in the accounting information in the banks under study. The number of recovered and valid questionnaires which were discharged was (88). The researcher analyzed the data using the Statistical Analysis Program (SPSS 20). At the end of this research, the researcher reached a number of conclusions, the most important of which is: There is a significant effect on the use of accounting information systems to improve the five dimensions of competitive advantage in the banks under study. The researcher also made a number of recommendations, including: The need to apply the accounting information systems in the banks under study, and the interest in training managers and employees and decision makers in the use of accounting information systems and increase their knowledge in the areas of computer use and related programs, and the management of the banks under study should work on continuous improvement of the type of technology used, facilities, equipment, equipment and technical and administrative equipment of these banks.